A Populus TIR1 gene family survey reveals differential expression patterns and responses to 1-naphthaleneacetic acid and stress treatments - Shu, Wenbo; Liu, Yingli; Guo, Yinghua; Zhou, Houjun; Zhang, Jin; Zhao, Shutang; Lu, Mengzhu (Frontiers in Plant Science, 2015)
The plant hormone auxin is a central regulator of plant growth. TRANSPORT INHIBITOR RESPONSE 1/AUXIN SIGNALING F-BOX (TIR1/AFB) is a component of the E3 ubiquitin ligase complex SCFTIR1/AFB and acts as an auxin co-receptor for nuclear auxin signaling. The SCFTIR1/AFB-proteasome machinery plays a central regulatory role in development-related gene transcription. Populus trichocarpa, as a model tree, has a unique fast-growth trait to which auxin signaling may contribute. However, no systematic analyses of the genome organization, gene structure and expression of TIR1-like genes have been undertaken in this woody model plant. In this study, we identified a total of eight TIR1 genes in the Populus genome that phylogenetically clustered into four subgroups, PtrFBL1/PtrFBL2, PtrFBL3/PtrFBL4, PtrFBL5/PtrFBL6 and PtrFBL7/PtrFBL8, representing four paralogous pairs. In addition, the gene structure and motif composition were relatively conserved in each paralogous pair and all of the PtrFBL members localized in the nucleus. Different sets of PtrFBLs were strongly expressed in the leaves, stems, roots, cambial zones and immature xylem of Populus. Interestingly, PtrFBL1 and 7 were expressed mainly in cambial and vascular tissues, respectively, indicating their potential roles in wood formation. Furthermore, Populus FBLs responded differentially upon exposure to various stresses. Collectively, these observations lay the foundation for further investigations into the potential roles of PtrFBL genes in tree growth and development.